ASAS KEPASTIAN HUKUM ATAS PUTUSAN MAHKAMAH KONSTITUSI NOMOR: 91/PUU-XVIII/2020 - Ningrum, Maya Puspita; Roza, Ahmad Fadly; Sari, Komala; Hariani, Riri Rezeki (Sekolah Tinggi Ilmu Hukum Graha Kirana, 2023)
AbstractThe Constitutional Court is an important institution in the Indonesian state administration. The Constitutional Court acts as a balanced institution according to the principle of mutual control, because the 1945 Constitution provides the authority to resolve power disputes between state institutions. In addition, through its authority to review laws that violate the 1945 Constitution, the Constitutional Court guarantees the fulfillment of citizens' constitutional rights and protects them from laws that may cause constitutional harm. Several community groups and individuals submitted judicial reviews to the Constitutional Court regarding the constitutional losses caused by the Job Creation Law Number 11 of 2020. the problem that will be discussed is the legal considerations of the Constitutional Court Decision Number: 91/PUU-XVIII/2020. It is hoped that this research will be useful as a reference in the advancement of legal science in Indonesia, especially in the field of Constitutional Law related to the legal analysis of the Constitutional Court Decision Number: 91/PUU-XVIII/2020 in the Case of the Formil Test of Law Number 11 of 2020 concerning Job Creation against the 1945 Constitution in Review of the Principles of Legal Certainty in Indonesia. It is hoped that this writing will also be useful for the community and legal practitioners and theorists.This research uses normative juridical, or library law research, as a methodology. Normative legal research is based on primary and secondary legal materials, namely research that refers to the norms found in laws and regulations, or the law is considered as what is written in law books. Constitutional Court Decision No. 91 / PUU-XVIII / 2020 is a decision that granted the formal examiner's request for Law Number 11 of 2020 concerning Job Creation with the verdict that Law Number 11 of 2020 concerning Job Creation does not have conditionally binding legal force and is contrary to the 1945 Constitution of the Republic of Indonesia because it is not intended not to be revised within 2 (two) years from the date of this decision. In terms of the legal certainty of Law Number 11 of 2020 concerning Job Creation after Constitutional Court Decision Number 91 / PUU-XVIII / 2020, this decision is the current law (ius constitutum). This is because the decision of the Constitutional Court cannot be compared or complained about. AbstrakMahkamah Konstitusi (MK) merupakan lembaga penting dalam ketatanegaraan Indonesia. Mahkamah Konstitusi berperan sebagai lembaga yang berimbang menurut asas saling mengontrol, karena UUD 1945 memberikan kewenangan untuk menyelesaikan sengketa kekuasaan antar lembaga negara. Selain itu, melalui kewenangannya untuk menguji undang-undang yang melanggar UUD 1945, MK menjamin terpenuhinya hak konstitusional warga negara dan melindunginya dari undang-undang yang dapat menimbulkan kerugian konstitusional. Beberapa kelompok masyarakat dan individu mengajukan judicial review ke Mahkamah Konstitusi terkait kerugian konstitusional yang ditimbulkan oleh UU Cipta Kerja Nomor 11 Tahun 2020. permasalahan yang akan dibahas mengenai pertimbangan hukum Putusan Mahkamah Konstitusi Nomor: 91/PUU-XVIII/2020. Diharapkan penelitian ini bermanfaat menjadi rujukan dalam kemajuan ilmu hukum di Indonesia, khususnya dalam bidang Hukum Tata Negara terkait dengan analisis hukum Putusan Mahkamah Konstitusi Nomor: 91/PUU-XVIII/2020 Dalam Perkara Uji Formil Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja Terhadap UUD 1945 Ditinjau dari Asas Kepastian Hukum di Indonesia. Diharapkan penulisan ini juga akan bermanfaat bagi masyarakat dan praktisi dan teoritisi hukum.Penelitian ini menggunakan yuridis normatif, atau penelitian hukum kepustakaan, sebagai metodologi. Penelitian hukum normatif didasarkan pada bahan hukum primer dan sekunder, yaitu penelitian yang mengacu pada norma-norma yang ditemukan dalam peraturan perundang-undangan, atau hukum dianggap sebagai apa yang tertulis dalam buku hukum. Putusan MK No. 91/PUU-XVIII/2020 merupakan putusan yang mengabulkan permohonan pengujin formil atas Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja dengan amar putusan Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja tidak mempunyai kekuatan hukum mengikat secara bersyarat dan bertentangan dengan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 karena tidak dimaksudkan untuk tidak dilakukan perbaikan dalam waktu 2 (dua) tahun sejak putusan ini diucapkandalam hal kepastian hukum dari Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja setelah Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020, putusan ini merupakan hukum yang berlaku saat ini (ius constitutum). Ini karena putusan Mahkamah Konstitusi tidak dapat dibandingkan atau dimintai komplain atasnya.